A meta-analysis of rates of return to agricultural R & D: ex pede Herculem? - Alston, Julian M.; Wyatt, T. J.; Pardey, Philip G.; Marra, Michele C.; Chan-Kang, Connie (International Food Policy Research Institute, 2000)
IFPRI has long argued that spending on agricultural research constitutes a sound investment in poverty reduction and agricultural and economic growth, through improvements in productivity. This argument is based partly on the reported evidence of high rates of return to agricultural research, typically believed to be in the range of 40–60 percent per year. Yet there continues to be controversy over whether these figures are to be believed, and over what they actually indicate. This study represents the first attempt to take a comprehensive look at all the available evidence on rates of return to investments in agricultural R&D since 1953, and the only attempt to do so in a formal statistical fashion. This report has compiled and documented the literature in ways that make it more accessible and more useful to other researchers and policymakers, as well as others interested in the evidence. The analysis reveals some systematic patterns and some sources of biases that make it easier to interpret the evidence and draw meaningful conclusions. (Excerpted from Summary by Per Pinstrup-Andersen)